Method for preparing carbon material through step-by-step hot melting of coal liquefaction residues

By treating coal liquefaction residues by a step-by-step thermal dissolution method, asphalt raw materials with different numbers of aromatic rings are prepared, which solves the problem of coal liquefaction residue treatment in the existing technology and realizes the efficient and low-cost preparation and application of carbon materials, which are suitable for supercapacitors, hydrogen fuel cells and other fields.

CN120698460APending Publication Date: 2025-09-26SHANDONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510871567.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The treatment of coal liquefaction residue in the existing technology has problems such as feeding difficulty, pipeline blockage, environmental pollution, cumbersome deashing process, high production cost, poor product performance and unstable properties of the prepared microporous carbon.

Method used

A step-by-step thermal dissolution method is used to thermally dissolve coal liquefaction residue with different solvents in a graded manner to obtain asphalt raw materials with different numbers of aromatic rings. Carbon materials with different functions and uses are then prepared through carbonization and activation, avoiding the acid washing and deashing steps, and the solvent can be recycled.

Benefits of technology

The high-value-added resource utilization of coal liquefaction residue has been achieved. The prepared carbon material has excellent performance, reduced cost, and the solvent is recyclable. The carbon material has stable properties and is suitable for supercapacitors, hydrogen fuel cells and other fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for preparing a carbon material through step-by-step hot melting of coal liquefaction residues, and belongs to the technical field of coal liquefaction residue recovery. The preparation method comprises the following steps: carrying out step-by-step hot melting on the coal liquefaction residues and a plurality of different solvents in a plurality of stages, and carrying out separation in each stage to respectively obtain asphalt raw materials with different aromatic ring numbers; and carbonizing and / or activating the asphalt raw materials with different aromatic ring numbers to obtain the carbon material. According to the method, coal liquefaction residues are used as raw materials, asphalt raw materials with different aromatic ring number distribution are obtained in a step-by-step hot melting mode, and the asphalt raw materials are respectively carbonized and activated to prepare carbon materials with different functions and purposes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coal liquefaction residue recovery, and in particular relates to a method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue and its application. Background Art

[0002] Liquefaction residue is a solid waste product from the direct coal liquefaction process, representing approximately 30% by weight of the raw coal. It primarily consists of heavy oil, asphaltene, unreacted coal, and spent catalyst. This high volume of waste is challenging to process. Its high ash and sulfur content makes it prone to swelling and agglomeration. Traditional utilization methods such as pyrolysis, gasification, and combustion can lead to problems such as difficult feeding, pipeline blockage, and environmental pollution.

[0003] CN109385286A discloses a continuous pyrolysis device suitable for direct coal liquefaction residue. This device is equipped with a freely movable metal rod within the reaction chamber. This allows the semi-coke produced by the pyrolysis of the direct coal liquefaction residue to be crushed online by the impact of the freely moving metal rod, facilitating the continuous pyrolysis of the direct coal liquefaction residue. However, cold feeding easily clogs the feed port, making continuous feeding difficult. Furthermore, the liquefied residue will still adhere to the inner wall of the pyrolysis furnace during the pyrolysis process, resulting in high maintenance costs.

[0004] CN118272864A discloses a coal liquefaction residue electrode and a preparation method. This method involves deashing the liquefied residue, adding additives such as ammonium chloride, ferric chloride, copper oxide, and nickel nitrate, and subjecting the mixture to a hydrothermal reaction at 120-300°C to produce liquefied residue coke. The liquefied residue coke is then mixed with graphite and the liquefied residue, followed by hot pressing at 100-500°C to form the resulting electrode green body. The resulting electrode is then pyrolyzed at 500-1300°C to produce the liquefied residue electrode. However, the acid washing and deashing process for the liquefied residue is cumbersome, incomplete, and difficult to recover. Consequently, the resulting liquefied residue electrode exhibits poor performance.

[0005] CN118993067A discloses an ultrafine mosaic structure isotropic coke-based porous carbon and its preparation method and application. The method uses medium and low temperature coal tar pitch as raw material, utilizes polar organic solvent thermal extraction to prepare asphalt component, places the asphalt component in a normal pressure reactor for liquid phase carbonization, introduces air for oxidative modification during the process, obtains ultrafine mosaic structure isotropic semi-coke, finally mixes the obtained ultrafine mosaic structure isotropic semi-coke with an activator, and activates under inert gas protection to obtain ultrafine mosaic structure isotropic coke-based porous carbon. Although the porous carbon prepared by this method has a high specific surface area and can improve the performance of supercapacitors when used as an electrode material, the pitch prepared with coal tar as raw material has problems such as many light components and ash in the tar, resulting in high separation costs. At the same time, the boiling point of coal tar and the distribution range of aromatic ring number are wide, and the prepared microporous carbon properties are unstable.

[0006] There are many problems with the treatment of coal direct liquefaction residue in the existing technology: (1) Its utilization methods such as pyrolysis, gasification, and combustion have problems such as feeding difficulties, pipeline blockage and environmental pollution, and the process cost is high. (2) Its pickling and deashing process is cumbersome, and the pickling solution is not easy to recover, which increases production costs; incomplete deashing results in poor product performance. (3) Asphalt prepared from coal tar as raw material has problems such as a large number of light components and ash in the tar. Adding separation procedures further increases production costs. (4) The boiling point and aromatic ring number distribution range of coal tar are wide, and the properties of the prepared microporous carbon are unstable.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] The purpose of the present invention is to provide a method for preparing carbon materials by step-by-step thermal dissolution of coal liquefaction residue. Coal liquefaction residue is used as raw material, and asphalt raw materials with different aromatic ring number distributions are obtained by step-by-step thermal dissolution. They are then carbonized and activated to prepare carbon materials with different functions and uses.

[0009] In order to achieve the above objectives, the present invention adopts the following technical solutions:

[0010] The present invention provides a method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue, comprising the following steps:

[0011] Coal liquefaction residue and several different solvents are heat-dissolved in several stages, and after separation in each stage, asphalt raw materials (heat-dissolved products) with different numbers of aromatic rings are obtained;

[0012] The asphalt raw materials with different numbers of aromatic rings are carbonized and / or activated to obtain the carbon material.

[0013] Preferably, the particle size of the coal liquefaction residue is less than 0.3 mm.

[0014] Optionally, the different solvents include one or more of n-hexane, cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, or coal liquefaction heavy oil. The order of adding the solvents for the stepwise thermal dissolution is generally n-hexane, cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, and coal liquefaction heavy oil.

[0015] Preferably, the solvents used in each stage of the step-by-step thermal dissolution include two or more different solvents.

[0016] Furthermore, the mass ratio of each level of coal liquefaction residue or hot melt to the corresponding solvent is 1:5-20.

[0017] Furthermore, when the solvent used includes two different solvents, the solvent includes a combination of one of n-hexane, cyclohexane, toluene, xylene, tetrahydrofuran or 1-methylnaphthalene and coal liquefaction heavy oil in a mass ratio of 2-10:1.

[0018] Furthermore, the temperature of the step-by-step thermal dissolution is 50-300° C.; the pressure of the step-by-step thermal dissolution is 0.1-6 MPa; and the time of the step-by-step thermal dissolution is 1-6 h.

[0019] Optionally, the carbon material includes microporous carbon for supercapacitors, spherical activated carbon, activated carbon fibers, or carbon materials for hydrogen fuel cell catalyst supports.

[0020] When the carbon material is microporous carbon for supercapacitors, the asphalt raw materials with different numbers of aromatic rings are pre-oxidized and then carbonized and / or activated to obtain the microporous carbon for supercapacitors.

[0021] Furthermore, the pre-oxidation temperature is 180-250°C, the carbonization temperature is 700-1000°C, and the activation temperature is 700-1000°C.

[0022] Furthermore, the pre-oxidation is carried out in air or oxygen-containing gas atmosphere; the pre-oxidation time is 2-8 hours.

[0023] Furthermore, the carbonization process is carried out at a heating rate of 2-10°C / min under a nitrogen or argon atmosphere.

[0024] Optionally, the activation includes physical activation or chemical activation; the activation temperature is 700-1000°C.

[0025] The physical activation method can be water vapor or CO2 activation, the temperature is 700-1000°C, the heating rate is 2-10°C / min, and the activation time is 1-2h.

[0026] The chemical method comprises adding an activator, wherein the activator is phosphoric acid or potassium hydroxide, the mass ratio of phosphoric acid to raw materials is 0.2-0.8:1, the mass ratio of potassium hydroxide to raw materials is 2-5:1, the temperature is 700-1000°C, the heating rate is 2-10°C / min, and the process is carried out under a nitrogen or argon atmosphere, and the activation time is 1-2h.

[0027] Preferably, the preoxidized asphalt with a low aromatic ring number distribution is added to the preoxidized asphalt with a high aromatic ring number distribution at a mass ratio of 1:5-10, mixed evenly, and then carbonized. The mixing is generally performed by ball milling.

[0028] The microporous carbon prepared by mixing asphalt with a low aromatic ring number distribution with asphalt with a high aromatic ring number distribution can further improve the structural parameters of asphalt-based microporous carbon with a high aromatic ring number distribution. Because the raw materials are stable in nature and have a uniform structure, the pore distribution of the obtained activated carbon is concentrated.

[0029] When the carbon material is spherical activated carbon, the asphalt raw materials with different numbers of aromatic rings are first subjected to thermal polycondensation to form balls, and then pre-oxidized, and then carbonized and / or activated to obtain the spherical activated carbon.

[0030] Furthermore, the thermal polycondensation into microspheres is performed by heating and stirring the asphalt raw materials with different numbers of aromatic rings at 180-280°C to melt them, loading a high-pressure reactor with a mass fraction of 1-10% surfactant aqueous solution, and slowly injecting the molten asphalt raw materials into the high-pressure reactor for heating and stirring to obtain microspheres. The temperature is 200-300°C, the reaction time is 2-10h, the stirring rate is 300-1000r / min, and the microspheres are vacuum dried at 50-200°C for 2-10h.

[0031] The conditions for the pre-oxidation, carbonization or activation are substantially the same as the corresponding pre-oxidation, carbonization or activation conditions for preparing the microporous carbon for supercapacitors.

[0032] Optionally, the surfactant is one of polyvinyl alcohol, polyethylene glycol, stearic acid, and Tween; further, the mass ratio of the asphalt raw material to the surfactant aqueous solution is 1:2-10.

[0033] When the carbon material is activated carbon fiber, the asphalt raw materials with different numbers of aromatic rings are first melt-spun, then pre-oxidized, and then carbonized and / or activated to obtain the activated carbon fiber.

[0034] Furthermore, the melt spinning is performed by melt-spinning the asphalt raw materials with different numbers of aromatic rings in a melt spinning machine to obtain asphalt fiber precursors in a nitrogen atmosphere, a temperature of 230-250° C., a pressure of 0.3-0.7 MPa, and a rotation speed of 200-500 r / min.

[0035] The conditions for the pre-oxidation, carbonization or activation are substantially the same as the corresponding pre-oxidation, carbonization or activation conditions for preparing the microporous carbon for supercapacitors.

[0036] When the carbon material is a carbon material for a hydrogen fuel cell catalyst carrier, magnesium oxide is added to the asphalt raw materials with different numbers of aromatic rings, and then the carbon material for a hydrogen fuel cell catalyst carrier is obtained by carbonizing, pickling, washing, activating, and graphitizing.

[0037] Furthermore, the mass ratio of the asphalt raw material to the magnesium oxide is 1:2-5, and the mass ratio of the carbonized product to the acid is 1:5-20.

[0038] Furthermore, the carbonization temperature is 700-1000°C, the activation temperature is 700-1000°C, and the graphitization temperature is 1600-2000°C.

[0039] Compared to existing technologies, the step-by-step hot melt proposed in this invention is ash-free and eliminates the need for acid washing and deashing. Different types of asphalt feedstock are obtained through the step-by-step hot melt process, and the solvent can be recycled, achieving high-value-added resource utilization of the liquefied residue. Electrodes prepared from this liquefied residue have high performance, and the solvent can be recycled, further reducing costs.

[0040] The proposed stepwise thermal dissolution method exhibits a gradual increase in aromatic ring count, resulting in stable properties, a uniform structure, and a concentrated pore distribution of the resulting activated carbon. The microporous carbon prepared by mixing a pitch with a low aromatic ring count distribution with a pitch with a high aromatic ring count distribution can further improve the structural parameters of the pitch-based microporous carbon with a high aromatic ring count distribution.

[0041] At the same time, the obtained asphalt raw materials with different numbers of aromatic rings can also be used to prepare a variety of other carbon materials, such as spherical activated carbon, activated carbon fiber, and carbon materials used as hydrogen fuel cell catalyst supports. DETAILED DESCRIPTION

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0043] It should be noted that the raw materials used in the present invention are all commercially available products. Any ratios not specified in the present invention may be any ratio. The units of the ratios not specified in the present invention are all mass ratios. Any technical details not specified in the present invention are all prior art.

[0044] Example 1

[0045] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0046] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and n-hexane was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and n-hexane was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, and the flow reaction was carried out for 2 h. The hot melt 1 was received at the outlet.

[0047] (2) Cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, coal liquefaction heavy oil, etc. are pumped in sequentially, and the reaction of step (1) is repeated respectively, wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent are all kept constant, to obtain hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 is 4, 5, 6, 7, 8, 9, and 10, respectively.

[0048] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 were placed in an oven at 180°C for pre-oxidation for 2 hours, taken out, placed in a tube furnace, heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere, and carbonized for 2 hours. They were then mixed with potassium hydroxide in a mass ratio of 1:4, and activated at a rate of 5°C / min to 900°C for 2 hours under a nitrogen atmosphere to obtain different types of asphalt-based microporous carbon.

[0049] According to the BET specific surface area test, the specific surface areas of the microporous carbons obtained from the thermal melt 1, thermal melt 2, thermal melt 3, thermal melt 4, thermal melt 5, thermal melt 6, and thermal melt 7 are 2995m 2 / g、2853m 2 / g、2766m 2 / g、2651m 2 / g、2561m 2 / g、2472m 2 / g、2321m 2 / g.

[0050] Example 2

[0051] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0052] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and n-hexane was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and n-hexane was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, and the flow reaction was carried out for 2 h. The hot melt 1 was received at the outlet.

[0053] (2) Cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, coal liquefaction heavy oil, etc. are pumped in sequentially, and the reaction of step (1) is repeated respectively, wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent are all kept constant, to obtain hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 is 4, 5, 6, 7, 8, 9, and 10, respectively.

[0054] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 were placed in an oven at 180°C for pre-oxidation for 2 hours and then taken out. Hot melt 1 was added to hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:10, placed in a tube furnace, heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere, carbonized for 2 hours, and mixed with potassium hydroxide at a mass ratio of 1:4, heated to 900°C at a rate of 5°C / min under a nitrogen atmosphere for activation for 2 hours to obtain different types of asphalt-based microporous carbon.

[0055] According to the BET specific surface area test, the specific surface areas of the microporous carbons obtained from the thermal melts 2, 3, 4, 5, 6 and 7 are 2882 m 2 / g、2796m 2 / g、2700m 2 / g、2599m 2 / g、2502m 2 / g、2403m 2 / g.

[0056] Example 3

[0057] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0058] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and n-hexane was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and n-hexane was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, and the flow reaction was carried out for 2 h. The hot melt 1 was received at the outlet.

[0059] (2) Cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, coal liquefaction heavy oil, etc. are pumped in sequentially, and the reaction of step (1) is repeated respectively, wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent are all kept constant, to obtain hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 is 4, 5, 6, 7, 8, 9, and 10, respectively.

[0060] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 were placed in an oven at 180°C for pre-oxidation for 2 hours and then taken out. Hot melt 1 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:10, and hot melt 2 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:5. The mixtures were placed in a tube furnace and heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere. After carbonization for 2 hours, the mixtures were mixed with potassium hydroxide at a mass ratio of 1:4, heated to 900°C at a rate of 5°C / min under a nitrogen atmosphere and activated for 2 hours to obtain different types of asphalt-based microporous carbon.

[0061] According to the BET specific surface area test, the specific surface areas of the microporous carbons obtained from the thermal melts 3, 4, 5, 6 and 7 are 2836 m 2 / g、2755m 2 / g、2631m 2 / g、2582m 2 / g、2512m 2 / g.

[0062] Example 4

[0063] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0064] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and n-hexane was pumped in at a flow rate of 3 mL / min. The mass ratio of the liquefied residue and n-hexane was controlled to be 1:8. The reaction temperature was adjusted to 250 °C, the reaction pressure was adjusted to 3 MPa, and the flow reaction was carried out for 1 h. The hot melt 1 was received at the outlet.

[0065] (2) Cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene, coal liquefaction heavy oil, etc. are pumped in sequentially, and the reaction of step (1) is repeated respectively, wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent are all kept constant, to obtain hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 is 4, 5, 6, 7, 8, 9, and 10, respectively.

[0066] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 were placed in a 200℃ oven for pre-oxidation for 2h and then taken out. Hot melt 1 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:10, and hot melt 2 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:5. The mixtures were placed in a tube furnace and heated to 700℃ at a rate of 3℃ / min under a nitrogen atmosphere. After carbonization for 2h, they were mixed with potassium hydroxide at a mass ratio of 1:4, heated to 900℃ at a rate of 3℃ / min under a nitrogen atmosphere and activated for 2h to obtain different types of asphalt-based microporous carbon. The specific surface areas of the microporous carbons obtained from the thermal melts 3, 4, 5, 6 and 7 are 2825 m 2 / g、2736m 2 / g、2623m 2 / g、2559m 2 / g、2497m 2 / g.

[0067] Example 5

[0068] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0069] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and a mixed solvent of n-hexane and coal liquefaction heavy oil with a mass ratio of 10:1 was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue to the mixed solvent was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, the flow reaction was carried out for 2 h, and the hot melt 1 was received at the outlet.

[0070] (2) Pumping in a mixed solvent of cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene and coal liquefaction heavy oil in a mass ratio of 10:1 in sequence, and finally pumping in pure coal liquefaction heavy oil, repeating the reaction of step (1), wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent remain unchanged, and obtaining hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 are 4, 5, 6, 7, 8, 9, and 10, respectively.

[0071] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 were placed in an oven at 180°C for pre-oxidation for 2 hours, taken out, placed in a tube furnace, heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere, and carbonized for 2 hours. They were then mixed with potassium hydroxide in a mass ratio of 1:4, and activated at a rate of 5°C / min to 900°C for 2 hours under a nitrogen atmosphere to obtain different types of asphalt-based microporous carbon.

[0072] According to the BET specific surface area test, the specific surface areas of the microporous carbons obtained from the thermal melt 1, thermal melt 2, thermal melt 3, thermal melt 4, thermal melt 5, thermal melt 6, and thermal melt 7 are 3002m 2 / g、2889m 2 / g、2809m 2 / g、2697m 2 / g、2609m 2 / g、2531m 2 / g、2321m 2 / g.

[0073] Example 6

[0074] A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue:

[0075] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and a mixed solvent of n-hexane and coal liquefaction heavy oil with a mass ratio of 10:1 was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue to the mixed solvent was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, the flow reaction was carried out for 2 h, and the hot melt 1 was received at the outlet.

[0076] (2) Pumping in a mixed solvent of cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene and coal liquefaction heavy oil in a mass ratio of 10:1 in sequence, and finally pumping in pure coal liquefaction heavy oil, repeating the reaction of step (1), wherein the flow rate, reaction temperature, pressure, time and the mass ratio of the hot melt and the solvent remain unchanged, and obtaining hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 respectively. Among them, hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, and hot melt 6 are respectively subjected to rotary evaporation to remove the organic solvent, and hot melt 7 is centrifuged to separate the organic solvent. The average number of aromatic rings of hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 are 4, 5, 6, 7, 8, 9, and 10, respectively.

[0077] (3) Hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 were placed in an oven at 180°C for pre-oxidation for 2 hours and then taken out. Hot melt 1 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:10, and hot melt 2 was added to hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 at a mass ratio of 1:5. The mixtures were placed in a tube furnace and heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere. After carbonization for 2 hours, the mixtures were mixed with potassium hydroxide at a mass ratio of 1:4, heated to 900°C at a rate of 5°C / min under a nitrogen atmosphere and activated for 2 hours to obtain different types of asphalt-based microporous carbon.

[0078] According to the BET specific surface area test, the specific surface areas of the microporous carbons obtained from the thermal melts 3, 4, 5, 6 and 7 are 2907 m 2 / g、2812m 2 / g、2705m 2 / g、2679m 2 / g、2523m 2 / g.

[0079] Example 7

[0080] The hot melts 1, 2, 3, 4, 5, 6, and 7 obtained in steps (1) and (2) of Example 1 were heated and stirred at 200°C to melt, respectively. A 5% polyethylene glycol aqueous solution was placed in an autoclave, and the molten asphalt raw material was slowly injected into the autoclave and heated and stirred to obtain microspheres. The mass ratio of the asphalt raw material to the surfactant aqueous solution was 1:2. The temperature was 300°C, the reaction time was 2 hours, and the stirring rate was 500 r / min. The microspheres were vacuum dried at 150°C for 5 hours and then heated at 250°C in an air atmosphere for curing and crosslinking for 2 hours. The temperature was then increased to 700°C in a nitrogen atmosphere at a heating rate of 5°C / min and carbonized for 2 hours. After carbonization, the mixture was mixed with potassium hydroxide at a mass ratio of 1:4 and activated by heating to 900°C in a nitrogen atmosphere at 5°C / min for 2 hours to obtain different types of asphalt-based spherical activated carbon.

[0081] According to the BET specific surface area test, the specific surface areas of the spherical activated carbons obtained from the hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 are 2779m 2 / g、2662m 2 / g、2512m 2 / g、2434m 2 / g、2310m 2 / g、2202m 2 / g、2106m 2 / g.

[0082] Example 8

[0083] The hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 obtained in steps (1) and (2) of Example 1 were added to magnesium oxide and stirred and mixed (the mass ratio of the hot melt to magnesium oxide was 1:2). The temperature was raised to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and carbonized for 2 hours. The carbonized sample was pickled with 6 mol / L hydrochloric acid, and the sample and hydrochloric acid were pickled at a mass ratio of 1:10 to remove magnesium oxide, and then washed with deionized water until neutral; the pickled sample was mixed with potassium hydroxide at a mass ratio of 1:4, and the temperature was raised to 900°C at 5°C / min under a nitrogen atmosphere for activation for 2 hours. The activated sample was graphitized at 2000°C under a nitrogen atmosphere for 2 hours to obtain a carbon material that can be used as a hydrogen fuel cell catalyst support.

[0084] According to the BET specific surface area test, the specific surface area of ​​the carbon materials obtained from the hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 is 1988m 2 / g、1903m 2 / g、1803m 2 / g、1710m 2 / g、1622m 2 / g、1503m 2 / g、1416m 2 / g.

[0085] Example 9

[0086] The hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6 and hot melt 7 obtained in steps (1) and (2) of Example 1 were melt-spun in a melt spinning machine to obtain asphalt fiber precursors, nitrogen atmosphere, temperature 230°C, pressure 0.5 MPa and rotation speed 300 r / min. The obtained asphalt fiber precursors were heated at 250°C in an air atmosphere for curing and crosslinking for 2 hours. Then, the temperature was raised to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and carbonized for 2 hours. After carbonization, the mixture was mixed with potassium hydroxide at a mass ratio of 1:4, and the mixture was heated to 900°C at a rate of 5°C / min under a nitrogen atmosphere for activation for 2 hours to obtain different types of activated carbon fibers.

[0087] According to the BET specific surface area test, the specific surface areas of activated carbon fibers obtained from thermal melt 1, thermal melt 2, thermal melt 3, thermal melt 4, thermal melt 5, thermal melt 6, and thermal melt 7 are 2735m 2 / g、2621m 2 / g、2497m 2 / g、2387m 2 / g、2268m 2 / g、2149m 2 / g、2005m 2 / g.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that the raw material is replaced with medium and low temperature coal tar pitch produced by Yan'an Energy Chemical (Group) Co., Ltd. The specific surface areas of the microporous carbons obtained from hot melt 1, hot melt 2, hot melt 3, hot melt 4, hot melt 5, hot melt 6, and hot melt 7 are 2337m 2 / g、2358m 2 / g、2477m 2 / g、2346m 2 / g、2038m 2 / g、1989m 2 / g、1824m 2 / g.

[0090] Comparative Example 2

[0091] The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and coal liquefaction heavy oil was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and the coal liquefaction heavy oil was controlled to be 1:8, the reaction temperature was adjusted to 200 ° C, the reaction pressure was adjusted to 2 MPa, the flow reaction was carried out for 2 hours, and the hot melt was received at the outlet. The hot melt and the organic solvent were separated by centrifugation. The hot melt was placed in an oven at 180 ° C for pre-oxidation for 2 hours, then taken out, placed in a tubular furnace, heated to 700 ° C at 5 ° C / min under a nitrogen atmosphere, carbonized for 2 hours, and then mixed with potassium hydroxide at a mass ratio of 1:4, heated to 900 ° C at 5 ° C / min under a nitrogen atmosphere for activation for 2 hours to obtain asphalt-based microporous carbon. The specific surface area of ​​the obtained microporous carbon is 1623 m 2 / g.

[0092] Comparative Example 3

[0093] The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and tetrahydrofuran was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and tetrahydrofuran was controlled to be 1:8. The reaction temperature was adjusted to 200°C, the reaction pressure was adjusted to 4 MPa, and the flow reaction was carried out for 2 hours. The hot melt was received at the outlet, and the hot melt and the organic solvent were separated by rotary evaporation. The hot melt was placed in a 200°C oven for pre-oxidation for 2 hours, then taken out, placed in a tubular furnace, and heated to 700°C at 3°C / min under a nitrogen atmosphere. After carbonization for 2 hours, it was mixed with potassium hydroxide at a mass ratio of 1:4, and heated to 900°C at 3°C / min under a nitrogen atmosphere for activation for 2 hours to obtain asphalt-based microporous carbon. The specific surface area of ​​the obtained microporous carbon is 1892m 2 / g.

[0094] Comparative Example 4

[0095] (1) The liquefied residue produced by the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor, and cyclohexane was pumped in at a flow rate of 1 mL / min. The mass ratio of the liquefied residue and cyclohexane was controlled to be 1:8. The reaction temperature was adjusted to 200 °C, the reaction pressure was adjusted to 2 MPa, and the flowing reaction was carried out for 2 h. The hot melt 1 was received at the outlet.

[0096] (2) Tetrahydrofuran and coal liquefaction heavy oil were sequentially pumped in and the reaction of step (1) was repeated, wherein the flow rate, reaction temperature, pressure, time, and mass ratio of the hot melt to the solvent remained unchanged, to obtain hot melt 2 and hot melt 3, respectively. Hot melt 1 and hot melt 2 were subjected to rotary evaporation to remove the organic solvent, and hot melt 3 was centrifuged to separate the organic solvent. The average number of aromatic rings in hot melt 1, hot melt 2, and hot melt 3 was 5, 8, and 10, respectively.

[0097] Hot melt 1, hot melt 2, and hot melt 3 were placed in an oven at 180°C for pre-oxidation for 2 hours, then taken out and placed in a tube furnace. The temperature was raised to 700°C at 5°C / min under a nitrogen atmosphere. After carbonization for 2 hours, they were mixed with potassium hydroxide at a mass ratio of 1:4, and the temperature was raised to 900°C at 5°C / min under a nitrogen atmosphere for activation for 2 hours to obtain different types of pitch-based microporous carbon. The specific surface areas of the microporous carbons obtained from hot melt 1, hot melt 2, and hot melt 3 were 2361m 2 / g、1972m 2 / g、1921m 2 / g.

[0098] Comparative Example 5

[0099] Liquefaction residue from the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor. Tetrahydrofuran (THF) was pumped in at a rate of 1 mL / min, maintaining a mass ratio of 1:8. The reaction temperature was adjusted to 200°C, the pressure to 4 MPa, and the flow reaction was continued for 2 hours. The hot melt was collected at the outlet and separated from the organic solvent by rotary evaporation. The hot melt was heated and stirred at 200°C to melt. A 5% polyethylene glycol aqueous solution was then added to the autoclave. The molten asphalt feedstock was slowly injected into the autoclave and heated and stirred to produce microspheres. The mass ratio of asphalt feedstock to surfactant aqueous solution was 1:2. The reaction temperature was 300°C, the reaction time was 2 hours, and the stirring rate was 500 rpm. The microspheres were vacuum dried at 150°C for 5 hours and then cured and crosslinked by heating at 250°C in an air atmosphere for 2 hours. The temperature was then increased to 700°C at a rate of 5°C / min under a nitrogen atmosphere for 2 hours. After carbonization, it was mixed with potassium hydroxide in a mass ratio of 1:4, and activated for 2 hours by heating to 900℃ at 5℃ / min under nitrogen atmosphere to obtain pitch-based spherical activated carbon. The specific surface area of ​​the obtained pitch-based spherical activated carbon was 1661m 2 / g.

[0100] Comparative Example 6

[0101] Liquefaction residue from the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor. Tetrahydrofuran (THF) was pumped in at a rate of 1 mL / min, maintaining a mass ratio of 1:8. The reaction temperature was adjusted to 200°C and the pressure to 4 MPa. The flow reaction was continued for 2 hours. The hot melt was collected at the outlet and separated from the organic solvent by rotary evaporation. Magnesium oxide (MgO) was added to the hot melt and mixed (the mass ratio of hot melt to MgO was 1:2). The sample was carbonized at a heating rate of 5°C / min to 700°C under a nitrogen atmosphere for 2 hours. The carbonized sample was then acid-washed with 6 mol / L hydrochloric acid (1:10 mass ratio) to remove the MgO and then washed with deionized water until neutral. The acid-washed sample was mixed with potassium hydroxide (1:4 mass ratio) and activated at a heating rate of 5°C / min to 900°C under a nitrogen atmosphere for 2 hours. The activated sample was graphitized at 2000℃ for 2h in a nitrogen atmosphere to obtain a carbon material that can be used as a catalyst support for hydrogen fuel cells. The specific surface area of ​​the obtained carbon material is 866m 2 / g.

[0102] Comparative Example 7

[0103] Liquefaction residue from the Shenhua Ordos coal direct liquefaction project was placed in a flowing hot melt reactor. Tetrahydrofuran (THF) was pumped in at a rate of 1 mL / min, maintaining a mass ratio of 1:8. The reaction temperature was adjusted to 200°C and the pressure to 4 MPa. The flow reaction was continued for 2 hours. The hot melt was collected at the outlet and separated from the organic solvent by rotary evaporation. The hot melt was melt-spun in a melt spinning machine to produce pitch fiber precursors under a nitrogen atmosphere at 230°C, a pressure of 0.5 MPa, and a rotation speed of 300 r / min. The resulting pitch fiber precursors were heated at 250°C in air for 2 hours to cure and crosslink. The temperature was then increased to 700°C under a nitrogen atmosphere at a rate of 5°C / min for 2 hours to carbonize the precursors. After carbonization, the precursors were mixed with potassium hydroxide at a mass ratio of 1:4 and activated by heating to 900°C under a nitrogen atmosphere at a rate of 5°C / min for 2 hours to produce activated carbon fibers. The BET specific surface area test showed that the specific surface area of ​​the activated carbon fiber was 1587 m 2 / g.

[0104] Table 1 is the comparative data of specific surface area of ​​different carbon material products in Examples and Comparative Examples

[0105] Table 1 Summary of specific surface areas of different carbon materials (m 2 / g)

[0106] Hot melt 1 Hot melt 2 Hot melt 3 Hot melt 4 Hot melt 5 Hot melt 6 Hot melt 7 Example 1 2995 2853 2766 2651 2561 2472 2321 Example 2 / 2882 2796 2700 2599 2502 2403 Example 3 / / 2836 2755 2631 2582 2512 Example 4 / / 2825 2736 2623 2559 2497 Example 5 3002 2889 2809 2697 2609 2531 2321 Example 6 / / 2907 2812 2705 2679 2523 Example 7 2779 2662 2512 2434 2310 2202 2106 Example 8 1988 1903 1803 1710 1622 1503 1416 Example 9 2735 2621 2497 2387 2268 2149 2005 Comparative Example 1 2337 2358 2477 2346 2038 1989 1824 Comparative Example 2 1623 / / / / / / Comparative Example 3 1892 / / / / / / Comparative Example 4 2361 1972 1921 / / / / Comparative Example 5 1661 / / / / / / Comparative Example 6 866 / / / / / / Comparative Example 7 1587 / / / / / /

[0107] As can be seen from Table 1, the different types of asphalt feedstock obtained by stepwise thermal dissolution using different solvents in Examples 1-6 not only achieve high-value-added resource utilization of the liquefied residue, but also exhibit significantly higher specific surface areas than the other feedstocks in Comparative Example 1, the non-stepwise thermal dissolution in Comparative Example 2, or the other solvents in Comparative Examples 3 and 4. A comparison of Examples 7, 8, and 9 with Comparative Examples 5, 6, and 7 also yields the same conclusion.

[0108] By comparing Example 1 with Examples 2 and 3, it can be seen that the microporous carbon prepared by mixing asphalt with a low aromatic ring number distribution with asphalt with a high aromatic ring number distribution can further improve the structural parameters of asphalt-based microporous carbon with a high aromatic ring number distribution.

[0109] By comparing Example 1 with Example 5 and Example 3 with Example 6, it can be seen that using different solvents and coal liquefaction heavy oil mixed solvent for thermal dissolution in each stage not only does not reduce the specific surface area of ​​the microporous carbon, but further increases it.

[0110] Finally, it should be noted that the above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will appreciate that the technical solutions described in the aforementioned embodiments may be modified, or some or all of the technical features therein may be replaced with equivalents. Such modifications or replacements do not deviate from the essence of the corresponding technical solutions within the scope of the technical solutions of the various embodiments of the present invention. Furthermore, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not others, the combination of features from different embodiments is intended to be within the scope of the present invention and to form different embodiments. For example, in the claims above, any of the claimed embodiments may be used in any combination. The information disclosed in this background section is intended solely to enhance understanding of the overall background technology of the present invention and should not be construed as an admission or any form of implication that such information constitutes prior art already known to those skilled in the art.

Claims

1. A method for preparing carbon materials by stepwise thermal dissolution of coal liquefaction residue, characterized in that: The steps include: Coal liquefaction residue and several different solvents are thermally dissolved in several stages, and after separation in each stage, asphalt raw materials with different aromatic ring numbers are obtained; The asphalt raw materials with different numbers of aromatic rings are carbonized and / or activated to obtain the carbon material.

2. The method according to claim 1, characterized in that The different solvents include one or more of n-hexane, cyclohexane, toluene, xylene, tetrahydrofuran, 1-methylnaphthalene or coal liquefaction heavy oil.

3. The method according to claim 2, characterized in that The solvents used in each stage of the step-by-step thermal dissolution include two or more different solvents; When the solvent used includes two different solvents, the solvent includes a combination of one of n-hexane, cyclohexane, toluene, xylene, tetrahydrofuran or 1-methylnaphthalene and coal liquefaction heavy oil in a mass ratio of 2-10:

1.

4. The method according to claim 1, wherein The temperature of the step-by-step thermal dissolution is 50-300°C; And / or, the pressure of the step-by-step thermal dissolution is 0.1-6 MPa.

5. The method according to any one of claims 1 to 4, characterized in that The carbon material includes microporous carbon for supercapacitors, spherical activated carbon, activated carbon fiber or carbon material for hydrogen fuel cell catalyst carriers.

6. The method according to claim 5, characterized in that When the carbon material is microporous carbon for supercapacitors, the asphalt raw materials with different numbers of aromatic rings are pre-oxidized and then carbonized and / or activated to obtain the microporous carbon for supercapacitors.

7. The method according to claim 6, characterized in that When the carbon material is microporous carbon for supercapacitors, pre-oxidized pitch with a low aromatic ring number distribution is added to pre-oxidized pitch with a high aromatic ring number distribution in a mass ratio of 1:5-10 and then carbonized.

8. The method according to claim 5, characterized in that When the carbon material is spherical activated carbon, the asphalt raw materials with different numbers of aromatic rings are first subjected to thermal polycondensation to form balls, and then pre-oxidized, and then carbonized and / or activated to obtain the spherical activated carbon.

9. The method according to claim 5, characterized in that When the carbon material is activated carbon fiber, the asphalt raw materials with different numbers of aromatic rings are first melt-spun, then pre-oxidized, and then carbonized and / or activated to obtain the activated carbon fiber.

10. The method according to claim 5, characterized in that When the carbon material is a carbon material for a hydrogen fuel cell catalyst carrier, magnesium oxide is added to the asphalt raw materials with different numbers of aromatic rings, and then carbonized, pickled, washed, activated, and graphitized to obtain the carbon material for a hydrogen fuel cell catalyst carrier.

Citation Information

Patent Citations

  • Continuous pyrolysis apparatus and continuous pyrolysis method for coal direct liquefaction residue

    CN109385286A

  • Coal liquefaction residue electrode as well as preparation method and application thereof

    CN118272864A